Eager for fairness or for revenge?: Psychological altruism in economics - Clavien, Christine; Klein, Rebekka A. (Economics and philosophy, 2010)
To understand the human capacity for psychological altruism, one requires a proper understanding of how people actually think and feel. This paper addresses the possible relevance of recent findings in experimental economics and neuroeconomics to the philosophical controversy over altruism and egoism. After briefly sketching and contextualizing the controversy, we survey and discuss the results of various studies on behaviourally altruistic helping and punishing behaviour, which provide stimulating clues for the debate over psychological altruism. On closer analysis, these studies prove less relevant than originally expected because the data obtained admit competing interpretations - such as people seeking fairness versus people seeking revenge. However, this mitigated conclusion does not preclude the possibility of more fruitful research in the area in the future. Throughout our analysis, we provide hints for the direction of future research on the question.